Re-recognize early recurrence of persistent atrial fibrillation - Fu, Kaixuan; Zhu, Xuefeng; Chu, Hongxia; Zhong, Lin; Wang, Zhen; Li, Wenjing; Wang, Chunxiao; Li, Jianping; Gong, Lei; Wang, Guangqiang; Yao, Rao; Wang, Lihong (Frontiers in Cardiovascular Medicine, 2023)
Aims: Few studies on early recurrence (ER) focused on patients with persistent atrial fibrillation (AF). We aimed to investigate the characteristics and clinical significances of ER in patients with persistent AF after catheter ablation (CA). Methods: A total of 348 consecutive patients who underwent first-time CA for persistent and long-standing persistent AF between January 2019 and May 2022 were investigated. Results: 5/348 (1.44%) patients who failed to convert to sinus rhythm after CA were excluded. 110/343 (32.1%) patients had ER, in which 98 (89.1%) were persistent and 50.9% occurred in the first 24h after CA. Compared with the patients without ER, those who with ER were more likely to have late recurrence (LR) (92.7% vs 1.7%, P < 0.001) during a median follow-up of 13 (IQR 6, 23) months. ER was the most significant independent predictor for LR (OR 120.5, 95% CI 41.5~349.8, P<0.001). ER as atrial flutter (AFL) had a lower risk of LR when compared with ER as AF (P=0.011) and AF&AFL (P=0.003). Early intervention of the patient with ER improved the short-term outcomes (P<0.001), not long-term outcomes. Only 22/251 (8.76%) patients of LR appears among these who had no recurrence in the first 1 month. Conclusions: Patients with persistent AF may not have a blanking period, but rather a risk period. The clinical significance of blanking period should be given differential treatment between paroxysmal AF and persistent AF.